2021
DOI: 10.1002/ski2.21
|View full text |Cite
|
Sign up to set email alerts
|

Multi parametric biophysical assessment of treatment effects on xerotic skin

Abstract: Background: Topical moisturizing products are widely used to alleviate the problems associated with xerotic skin. Their use affects many properties of the stratum corneum (SC) in a complex and interrelated manner. The range of measurement techniques available to the researcher has increased in recent years. However, few studies have looked for correlations between the different techniques for assessing how aspects of xerotic skin change over time as a result of topical moisturizer usage. Objectives: A 3-week i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Hydration of the skin helps to improve dryness and associated symptoms [6]. In fact, previous studies showed that moisturizers or emollients increase skin surface hydration and alleviate dry skin symptoms, but their effectiveness depends on their composition [4,7,8]. Specifically, there is still an unmet need for facial moisturizers satisfying consumers of different ethnicities [3].…”
Section: Introductionmentioning
confidence: 99%
“…Hydration of the skin helps to improve dryness and associated symptoms [6]. In fact, previous studies showed that moisturizers or emollients increase skin surface hydration and alleviate dry skin symptoms, but their effectiveness depends on their composition [4,7,8]. Specifically, there is still an unmet need for facial moisturizers satisfying consumers of different ethnicities [3].…”
Section: Introductionmentioning
confidence: 99%
“…Dry skin or xerosis may be associated with the onset of severe skin diseases such as AD or ichthyosis vulgaris [33]. An important common feature in xerosis and AD is the decrease in the synthesis of skin lipids (cholesterol, free fatty acids, and ceramides) and the resulting decreased formation of ICLL as a result of the lack of lipids and the necessary processing enzymes in the skin barrier [34].…”
Section: Discussionmentioning
confidence: 99%
“…Five readings were taken per test area and assessment time. The highest and lowest were removed, and the mean of the remaining three readings was used as an actual measurement value for further analysis, as reported before [12]. Subjects could not enter the study if they suffered from any skin condition at the test areas that might influence the interpretation of study data; a condition requiring the use of drugs interfering with study results within 1 week (immunosuppressive drugs, antihistamines, any topical medication at the test areas) or within 3 days (anti-inflammatory agents, analgesics with the exception of acetylsalicylic acid and paracetamol) before or during the study; or had allergies to cosmetic products or ingredients.…”
Section: Assessmentsmentioning
confidence: 99%
“…Five readings were taken per test area and assessment time. The highest and lowest were removed, and the mean of the remaining three readings was used as an actual measurement value for further analysis, as reported before [12].…”
Section: Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation